Factors of Providing Food and Economic Security of the State and Its Regions - Novoselova, Natalya N.; Krasnyuk, Lyudmila V.; Sukhorado, Yulia A.; Dzagoyeva, Marina R.; Aylarova, Zalina K. (International Review of Management and Marketing, 2016)
The present article highlights the development of the theoretical and methodological approaches to definition of subject domain of regional economy and ensuring stability of regional development. The main subject of this research is the grain production complex as reproduction system, taking into account its role in ensuring food security of the country and its regions. Results of research offer the effective proof to that the grain independence represents the function from the existing solvent demand of the population for food. In the absolute parameters, it is sufficient for full providing which allows the effectively usage of stimulation factors of grain farm development within policy of national security. It also becomes a major factor of providing food and economic security of the state and its regions in modern conditions. Keywords: regional development, reproduction, grain independence, sustainable development JEL Classifications: P25; Q01